2020
DOI: 10.1038/s41598-020-68310-w
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of interim PET/CT response for the treatment of advanced-stage marginal zone lymphoma in the post-rituximab era

Abstract: There are still controversies about the use of interim positron emission tomography/computed tomography (PET/CT) in indolent non-Hodgkin lymphoma due to the variable fluorodeoxyglucose (FDG) avidity. Therefore, this study aimed to evaluate the roles of interim PET/CT in marginal zone lymphoma (MZL), a representative indolent lymphoma. We analyzed the data of 146 MZL patients. All were treated with rituximab-containing immunochemotherapy. Interim PET/CT scan was performed after 2-3 cycles of therapy, and the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…A total of 38 articles investigated response assessment via early 18 F-FDG PET/CT imaging in the anti-CD20 immunotherapy, and of these, 19 studies were included in the meta-analysis (Supplemental Table 2 ) [ 16 , 18 , 21 23 , 25 27 , 29 35 , 38 46 , 48 57 , 59 69 , 71 78 , 80 92 , 96 106 ]. The meta-analysis was carried out on the DS, IHP, and ΔSUVmax for PFS and OS, and the obtained results are depicted as forest plots in Figs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 38 articles investigated response assessment via early 18 F-FDG PET/CT imaging in the anti-CD20 immunotherapy, and of these, 19 studies were included in the meta-analysis (Supplemental Table 2 ) [ 16 , 18 , 21 23 , 25 27 , 29 35 , 38 46 , 48 57 , 59 69 , 71 78 , 80 92 , 96 106 ]. The meta-analysis was carried out on the DS, IHP, and ΔSUVmax for PFS and OS, and the obtained results are depicted as forest plots in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported that interim 18 F-FDG PET/CT could have a key role in survival prediction and early response assessment of patients with lymphoma treated with anti-CD20 therapy [ 21 , 38 , 48 , 49 , 55 , 56 , 64 , 80 , 99 , 100 , 106 ]. In contrast, several studies reported a poor positive predictive value in early response assessment [ 45 , 46 , 54 , 60 , 66 , 72 , 97 , 104 ], whereby the interpretation of the 18 F-FDG PET/CT scan is of special importance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…17 , 18 In response assessment, Song et al highlighted the prognostic value of a Deauville score-base interim 18 FDG-PET/CT response assessment on PFS in a set of 146 patients and across all subtypes (but mostly EMZL and NMZL). 19 In this paper, ∆SUVmax had no prognostic impact and TMTV was not assessed. Finally, Vaxman et al reported the prognostic role of SUVmax value at end-of-treatment on PFS in a set of 110 patients.…”
mentioning
confidence: 84%